Optimalisasi Teknologi Dalam Administrasi Paud: Efektivitas Aplikasi Sippa Dalam Pencatatan Tumbuh Kembang Anak - Afrianingsih, Anita; Zulfahmi, M. Nofan; As’ad, Ali; Rufiati, Alfina; Pratiwi, Dewi; Amalia, Dina (Forum Kerjasama Pendidikan Tinggi, 2026)
Systematic monitoring of children's growth and development is very important for early childhood educators. However, many PAUD institutions still record child development manually, which is less efficient, and risks data accuracy. Technology integration is the right solution to answer these challenges. This community service aims to improve the ability of teachers to utilize information technology to monitor children's growth and development, optimizing the recording of developmental data through the SIPPA application. This activity is carried out in stages; Preparation, socialization, technical training, implementation of SIPPA use practices, monitoring, and evaluation. The subjects of this activity are all teachers of Baiturrohim Kindergarten. The results of the activity showed a significant increase in the capacity of Baiturrohim Kindergarten teachers in managing child development data digitally. The teachers showed high enthusiasm for the integration of technology in the administrative process of documenting children's growth and development. In addition, this activity also has a positive impact on the institution as a whole, because the recording system becomes more organized, transparent, and easily accessible when needed. In the future, it is hoped that teachers' ability to use the SIPPA application can continue to be developed in an ongoing manner, so that recording children's development is not only an administrative obligation, but also an important instrument in designing learning that is more targeted and based on actual data.